Phenytoin-induced acute hypersensitivity pneumonitis - Pallavi Periwal; Sharad Joshi; Rajesh Gothi; Deepak Talwar (Lung India, 2015)
Lungs are target organs for toxic effects of various drugs due to many reasons. Diphenylhydantoin (DPH) is reported to have many extrapulmonary side effects. We are presenting a case of acute hypersensitivity pneumonitis (HP) secondary to DPH, presenting with respiratory failure. Acute HP with respiratory failure is an uncommon drug side effect of the DPH therapy and is a diagnosis of exclusion. It requires detailed workup and exclusion of other causes along with evidence of improvement in the patient's condition after withholding DPH.